Spatio-temporal distribution of CO2 mixing ratio over Bhubaneswar, Varanasi and Jodhpur of India– airborne campaign, 2016. (15th March 2019) - Sreenivas, G.; Mahesh, P.; Biswadip, G.; Suresh, Sripada; Rao, P.V.N.; Chaitanya, M. Krishna; Srinivasulu, P.
Abstract: Airborne measurements of vertical distribution of atmospheric CO2 were conducted over India in 2016 from a Super King Beechcraft 200 aircraft of National Remote Sensing Centre (NRSC), Hyderabad, employing a LICOR-7200 (LI-7200) instrument for high frequency CO2 /H2 O measurements and a Trimble 5700 GPS receiver for geo-tagging them. The present study analyzes the spatio-temporal distribution of CO2 mixing ratios over the cities of Bhubaneswar, Varanasi and Jodhpur during June 2016. Measurements were conducted over each location for up to 5 days each, between 0900 and 1400 h local time. Significant variation was observed in the vertical and horizontal spatial distribution of CO2 from surface to 3.2 km altitude, which was the maximum height at which the aircraft was flown, over all locations. Inter-comparison of airborne measurements against satellite remote sensing retrieved CO2 profiles from the Infrared Atmospheric Sounding Interferometer (IASI) showed underestimation of IASI by 0.5–1.5% (3–6 ppm) to an overestimation of up to 5% (about 15 ppm), with the Pearson correlation coefficient 'r' between airborne and IASI retrieved CO2 varying from 0.34 to 0.95 respectively. The mean relative bias between airborne and satellite measured CO2 profiles are within 1–4%. A variation of 5–15 ppm was observed between dry and wet CO2 measurements, indicating the strong influence of water vapor on CO2 mixing ratios. The CO2 mixing ratio with corresponding altitudes [ maximum CO 2 ( height ) minimum CO 2 ( height ) ] over Bhubaneswar, Varanasi and Jodhpur were [ 412.43 ± 8.23 ppm ( 1000 m ) 389.42 ± 2.66 ppm ( 2800 m ), 420.34 ± 15.82 ppm ( 800 m ) 386.89 ± 7.82 ppm ( 3200 m ), 405.74 ± 6.77 ppm ( 200 m ) 383.42 ± 5.58 ppm ( 3200 m ) ] respectively. Highlights: Horizontal and vertical mixing of CO2 was captured with 2-D linear resampling method. The 'r' between airborne and satellite measured CO2 are varies from 0.34 to 0.95. Relative bias between satellite and airborne measured CO2 was between 1 and 4%. The H2 O correction was resulted 5–15 ppm difference between wet and dry air CO2 . Influence of air mass on vertical CO2 was from the NW direction of the study sites.